Substantiation of parameters and operational modes of air solar collector - Korobka, Serhiy; Babych, Mykhailo; Krygul, Roman; Zdobytskyj, Andriy (Eastern-European Journal of Enterprise Technologies, 2018)
We developed a new design of an air solar collector for a fruit dryer including double glazing and a selective surface made of a thin metal substrate with inlet and outlet openings on its bottom. We established that it is necessary to use a glass with a heat-reflecting coating of a solid K-glass type with a radiation coefficient ε=0.1...0.15 for a double-glazing substrate. This makes it possible to obtain the widest possible spectrum of direct sunlight rays that irradiate a surface of an absorbing plate and reduces a diffuse component of radiation, which ensures an increase in efficiency of a solar collector. We determined regularities of the influence of a change in flow speed of a heat-transfer agent, a temperature drop, and radiation intensity on power of a solar collector. We developed a model of heat exchange processes occurring in an air solar collector. We presented the methodology for estimation of heat loss of an air solar collector with passive use of solar energy. We established that energy illumination E, which is from 377 to 1,223 W/m2, affects heat output of an air collector Q=117...480 W significantly. We established that a use of a non-selective absorbing surface in an air solar collector with a low insolation level E=377 W/m2 makes it possible to increase efficiency by η=70.7 % more for selective, and at a large energy illumination of E=1,000 W/m2, on the contrary small η=54.6 %. This makes it possible to explain how redistribution of the ratio of the maximum current thermal power (NSC=48.8...100 W) and efficiency of an air solar collector occurs. One can use the obtained results in development and improvement of technical means for fruit drying to improve technological and energy efficiency of the process.